2011
DOI: 10.1530/eje-10-0969
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Extra-hepatic acromegaly: a new paradigm?

Abstract: Medical treatment of acromegaly with long-acting somatostatin analogs (LA-SMSA) and the GH receptor antagonist, pegvisomant (PEGV), has made it possible to achieve normal serum IGF1 concentrations in a majority of patients with acromegaly. These two compounds, however, impact the GH-IGF1 axis differently, which challenges the traditional biochemical assessment of the therapeutic response. We postulate that LA-SMSA in certain patients normalizes serum IGF1 levels in the presence of elevated GH actions in extra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 54 publications
2
35
1
4
Order By: Relevance
“…16 This observation may be attributed to a GH-independent suppressive effect of SSAs on hepatic IGF-I production. 26 The present study confirmed a significantly higher frequency of discordant GH and IGF-I values among patients who received SSAs vs non-SSAtreated patients (32Á5% vs 21Á6%). However, regarding the pattern of discordance, the 'High IGF-I' type of discordance was more common among patients under SSA treatment, probably reflecting the fact that SSAs powerfully suppress GH pulses, but have only limited effect on basal GH secretion.…”
Section: Discussionsupporting
confidence: 81%
“…16 This observation may be attributed to a GH-independent suppressive effect of SSAs on hepatic IGF-I production. 26 The present study confirmed a significantly higher frequency of discordant GH and IGF-I values among patients who received SSAs vs non-SSAtreated patients (32Á5% vs 21Á6%). However, regarding the pattern of discordance, the 'High IGF-I' type of discordance was more common among patients under SSA treatment, probably reflecting the fact that SSAs powerfully suppress GH pulses, but have only limited effect on basal GH secretion.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, a new concept of extrahepatic acromegaly induced by SSTA has been introduced. It is postulated by Neggers et al (37) that long-acting SSTA normalize serum IGF1 levels in certain patients in the presence of elevated GH actions in extrahepatic tissues. Also, Rubeck et al (38) compared traditional and novel biomarkers and health status in patients with acromegaly treated with either surgery alone or SSTA.…”
Section: Discussionmentioning
confidence: 99%
“…Neggers et al (39) summarised these observations in their hypothesis of an extra-hepatic acromegaly. SSA decreases not only the GH levels of the pituitary but also reduces the insulin production from the pancreatic b-cells.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%